ENGLISH VOICE AND ITS PROSODIC CHARACTERISTICS IN TEACHING ORAL INTERPRETATION - Tetiana Yeremenko; Angelina Demchuk; Iryna Lukyanchenko (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2020)
The research concerns the problem of mastering English voice production skills in oral interpretation of the authentic belles-lettres texts. The purpose of the paper is to present the teaching algorithm of training future English language and literature teachers' skills in decoding and orally interpreting verbalised English voice prosodic characteristics. The authors argue the necessity of training future English teachers in mastering their voices on the basis of the mechanism of English voice perception in order to make them sound English. The research represents the results of experimental teaching English voice production skills to the 4th year BA students at South-Ukrainian National Pedagogical University named after K. D. Ushynsky. The participants were 60 students - future English language and literature teachers - who agreed to take part in the research. Data analysis tools comprise pedagogical observation, questionnaires, testing for skills level assessment, expert assessment of testing results, statistical and mathematical processing of obtained data. The experimental teaching included three stages: diagnostic (entry testing), empirical training (teaching algorithm implementation) and checkout (final testing). The obtained results prove that the suggested four-stepped teaching algorithm in "Oral interpretation of the text" successfully starts in students the mechanism of the English voice perception, develops their ability to decode verbalised English voice prosodic characteristics and their functions in the process of philological reading, and forms future English language and literature teachers' specific skills in English voice modulation in oral interpretation.